The Standardization of Ethanolic Extract of Tahongai Leaves (Kleinhovia hospita L.) - Indah Solihah; Mardiyanto Mardiyanto; Soilia Fertilita; Herlina Herlina; Oktia Charmila (Science and Technology Indonesia, 2018)
Extract is basic material for herbal drug. The formulation of herbal drugs requires consistent of biological activity, a consistent chemical profile, or simply a quality assurance programs that can be achieved by standardizing extracts. The leaves of tahongai (Kleinhovia hospita L.) have been traditionally used in Komering tribes as phytotherapy to cure the inflammation related diseases including cancer, furuncles, polyps and tonsillitis. The aim at this study was to standardize the quality of tahongai leaves ethanolic extract by determining the specific and non specific parameters of ethanolic extract of Tahongai leaves (Kleinhovia hospita L.). The Preliminary phytochemical analysis revealed presence of alkaloids, flavonoids, saponins, tanins, and steroids in extract. The result of specific parameters extracts showed that the organoleptic properties of ethanolic extract of tahongai leaves were thick, brownish black in color, has characteristic odor, astringent with slightly bitter taste, the water and ethanol soluble extractive content were 19.263% ± 0.95 and 18.30% ± 0.51 respectively. The non specific parameters of tahongai leave ethanolic extract showed the density of extract was 1.413 g/mL ± 0.04, the water content value of 21.16% ± 0.55, total ash content 15.64% ± 0.75, acid insoluble ash content 8.282% ± 0.28, Pb contamination content 3,67 ppm, Cd contamination content <0,0043 ppm, total bacteria contamination 90.5 x 101 colony/g, and the total mold and yeast contamination of 1 x 101 colony/g.